Pride versus prejudice : Jewish doctors and lawyers in England, 1890-1990 - Cooper, John, 1935- (Littman library of Jewish civilization (Series), 2003)
This pioneering study, based on a wide range of sources and supported by numerical data, illustrates the lives and professional experiences of the individuals involved.